Time-dependent changes in distribution of basic fibroblast growth factor immunoreactive cells in rat hippocampus after status epilepticus - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2007)
Objective: In this study, we aimed to examine time-dependent morphologic changes and quantitative alterations in the density of basic fibroblast growth factor (bFGF)-immunoreactive (ir) astrocytes and CA2 pyramidal neurons in dorsal hippocampus of rats after status epilepticus (SE) induced by kainic acid (KA) injection. Methods: Wistar albino rats were injected with saline or KA i.p. to investigate time-dependent alterations in morphology and the number of bFGF-ir astrocytes and neurons in the dorsal hippocampus 15, 30 and 90 days after KA injection. Results: Fifteen days after KA injection, gliosis was present throughout the hippocampus and neuronal loss was evident in CA1 and CA3 regions, which was more severe after 30 and 90 days. KA-injected rats demonstrated significantly increased number of both bFGF-ir astrocytes throughout the hippocampus and pyramidal neurons in CA2 after 15 days and decreased number after 30 and 90 days. Conclusion: The decrease in the number of bFGF-ir astroglia and neurons in long term after KA injection may indicate a decrease in the production of bFGF and/or number of bFGF-ir cells, suggesting that protective effects of bFGF might be altered during epileptogenesis in the hippocampus.
Keywords: bFGF; hippocampus; kainic acid; rat; mature; immunohistochemistry; TEMPORAL-LOBE EPILEPSY; AMMONS HORN SCLEROSIS; KAINIC ACID; KAINATE INJECTION; NERVOUS-SYSTEM; BRAIN-DAMAGE; SEIZURES; NEURONS; MECHANISMS; INDUCTION